CORPORATE SOCIAL RESPONSIBILITY DAN EARNINGS MANAGEMENTS: SUDUT PANDANG STAKEHOLDER THEORY - Novi Kantasilo Tan; Permata ayu widyasari; Maria Eugenia Hastuti (STIE Muhammadiyah Jakarta, 2020)
This study aims to examine the effect of corporate social responsibility on earnings management. Earnings management, as the dependent variable, is proxied by discretionary accruals (DACC). While corporate social responsibility, as an independent variable, is measured by adjusted GRI standards. This study uses sample manufacturing companies listed on the Indonesia Stock Exchange during the period 2012-2016. The number of samples used in this study amounted to 423. The findings, based on the linear regression method, indicate that corporate social responsibility has a significant negative effect on earnings management. To conform to the result, a robustness test was performed and found a significant negative relationship between dummy corporate social responsibility and earnings management. Dummy 1 for the company which disclose CSR above average, 0 for the company disclose CSR below average. So it can be concluded that the company that focuses on corporate social responsibility has lower earnings management. For leverage, size, and ROA, as control variables, showed no significant effect on earnings management.